Production of components with plaster residue and sodium citrate: physical, mechanical, rheological analysis - Silva, Deborah Grasielly Cipriano da (ANTAC - Associação Nacional de Tecnologia do Ambiente Construído, 2019)
The construction industry, a major influencer in Brazil’s economic and social development, is responsible for a large consumption of raw materials and waste production. In particular, plaster presents significant growth, especially in the Northeast, due to the region of Araripe, great producer of this construction material. Considering the serious problems caused by the incorrect disposal of plaster in nature, there is the challenge of its recycling process. This research aimed to analyze several percentages of plaster residues to be added to the plaster paste, with and without retarder additive (sodium citrate), in terms of physical, mechanical, and rheological properties, focusing at the production of components. For that, the residue underwent physic-chemical recycling process to be replaced by plaster or by mass, in the percentages of 25%, 50%, 75% and 100%. The study of the performance of the material was done through the tests of granulometry, unit mass, mini-slump method, calorimetry, squeeze-flow method, compressive strength, and surface hardness. The results showed that the recycled plaster (RP) did not excessively damage the studied properties, and it was permissible to substitute up to 50% of RP in the production of the paste for components, following the recommendations of the recycling process and water/plaster ratio.